If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(10x+5)=-2(-3x-6)
We move all terms to the left:
4(10x+5)-(-2(-3x-6))=0
We multiply parentheses
40x-(-2(-3x-6))+20=0
We calculate terms in parentheses: -(-2(-3x-6)), so:We get rid of parentheses
-2(-3x-6)
We multiply parentheses
6x+12
Back to the equation:
-(6x+12)
40x-6x-12+20=0
We add all the numbers together, and all the variables
34x+8=0
We move all terms containing x to the left, all other terms to the right
34x=-8
x=-8/34
x=-4/17
| 4.5(−1.5)=x | | -6x+5(-3x-18)=141 | | 2(6−2x)+1=25. | | 15n-2=35 | | 3/5x2-2/3x+1=0 | | 15-2n=35 | | -20+6x=8x+40 | | 66=m+51 | | 9(2+3x)= | | x=-2x^2+5 | | -16-3x=-67 | | 6(3x+4)=3(7x+1) | | 11=5x-15-5 | | 4.5y+4-3y=15.5 | | f=-2(5)^2+5 | | 0.2(d-6=0.3d+5-3+0.1d | | 0.16x=21 | | 4r^2-r-4=0 | | f=-10^2+5 | | 0.16x=12 | | 0.16+12=x | | Y=-6.2x+64 | | 3(x+3)=-10(x+2) | | 1/5x+29/5= | | 15x+295= | | 47+2x+1=95 | | 47+2x+1=85 | | 47+2x+1=90 | | F(t)=21+4t | | -4(8k+8)=48-36k | | -77=-7x-5(-2x+10) | | 10b+2=6b+4 |